Description of six new species of the genus Ripeacma (Lepidoptera: Oecophoridae) from China, with a checklist of the world species - Li, Suran; Wang, Shuxia (Zootaxa, 2017)
Six new species of the genus Ripeacma Moriuti, Saito & Lewvanich, 1985 are described: R. rostratiformis sp. nov. from Hainan, R. angustizonalis sp. nov. from Guangdong, Guangxi and Hainan, R. fusoidea sp. nov. from Yunnan, R. lunata sp. nov. from Guizhou, R. ventilatiformis sp. nov. from Hong Kong and Hainan, and R. sentosa sp. nov. from Guangxi; three species are newly recorded for China: R. yaiensis Moriuti, Saito & Lewvanich, 1985, R. nangae Moriuti, Saito & Lewvanich, 1985 and R. tirawati Moriuti, Saito & Lewvanich, 1985. Images of adults and genitalia of the new species are provided. A checklist of the Ripeacma species is given on a worldwide basis.